Implementation of ADDIE Model in Improving the Ability of Lecturers to Write Scientific Articles in Accredited Journals - Wibawa, Arif; Ashrianto, Panji Dwi; Pambudi, Sigit Tri (RSF Conference Series: Business, Management and Social Sciences, 2021)
The writing ability of the lecturers of the Communication Studies Study Program still needs to be improved considering that the number of scientific articles written by the UPN "Veteran" Yogyakarta lecturers in general and the lecturers of the Communication Studies Study Program, in particular, is still tiny, so it is deemed necessary to carry out specific assessments of the lecturers so that the number of scientific articles written in Accredited journals is increasing. Improving the writing ability of lecturers in accredited journals is carried out through training with the Addie model. This study aims to find out how the Addie model is used by the Communication Studies Study Program to improve the pedagogic competence of lecturers in terms of the ability to write accredited journals. Using the Research and Development (RnD) approach through the stages of the ADDIE model, this study involved 30 lecturers of the Department of Communication Sciences UPN "Veteran" Yogyakarta as participants. The results of this study are the training model. The developed training model is quite effective in increasing the ability of participants to write and produce scientific papers of international standard. This can be seen from the changes in the contents of the manuscripts submitted before and after the training and the assessment carried out by the supervisors, which showed significant progress in the quality of the participants' writings. The training activities also increased the perception of lecturers in the Department of Communication Sciences UPN Veteran Yogyakarta regarding their ability to write scientific papers for international publications.